Removal of U(VI) from nuclear mining effluent by porous hydroxyapatite: Evaluation on characteristics, mechanisms and performance. (November 2019) - Su, Minhua; Tsang, Daniel C.W.; Ren, Xinyong; Shi, Qingpu; Tang, Jinfeng; Zhang, Hongguo; Kong, Lingjun; Hou, Li'an; Song, Gang; Chen, Diyun
Abstract: The effluents from nuclear mining processes contain relatively high content of radionuclides (such as uranium), which may seriously threaten the environment and human health. Herein, a novel adsorbent, porous hydroxyapatite, was prepared and proven highly efficient for removal of uranyl ions (U(VI)) given its high U(VI) uptake capacity of 111.4 mg/g, fast adsorption kinetics, and the potential stabilization of adsorbed U(VI). A nearly complete removal of U(VI) was achieved by porous HAP under optimized conditions. Langmuir model could well describe the adsorption equilibrium. The data fit well with pseudo-second-order kinetic model, suggesting that U(VI) adsorption is primarily attributed to chemisorption with porous HAP. Intraparticle diffusion analysis showed that the intraparticle diffusion is the rate-limiting step for U(VI) adsorption by porous HAP. After removal by porous HAP, the adsorbed U(VI) ions were incorporated into tetragonal autunite, which has a low solubility (log Ksp: −48.36). Our findings demonstrate that the porous HAP can effectively remediate uranium contamination and holds great promise for environmental applications. Graphical abstract: Image 1 Highlights: Porous HAP was facilely fabricated for the adsorption-based separation process. The removal of U(VI) can be efficient obtained with uptake capacity of 111.4 mg/g. The intraparticle diffusion is the restriction step for U(VI) adsorption. Adsorption mechanism reveal U(VI) ions were incorporated into tetragonal autunite. The cleanup process is environmentally friendly and economically feasible.